Strategic Marketing Analysis of IndiHome as a Leading Provider of Telecommunications and Multimedia Services in Jakarta - Sosidah, Sosidah; Rojikun, Ahmad; Tarmizi, Achmad; Rohman, Abdul; Riyadi, Selamet (Jurnal Ilmiah Multidisiplin Indonesia (JIM-ID), 2025)
This study aims to analyze the strategic marketing efforts of IndiHome as a leading telecommunications and multimedia provider in Jakarta. Through a SWOT framework supported by internal and external factor evaluations (IFE and EFE), the research identifies IndiHome’s strengths, including its wide-reaching fiber-optic network, strong financial backing, and qualified human resources. However, the company faces challenges such as inconsistent customer service and sudden policy changes that affect user satisfaction. The study also highlights external opportunities in technological advancement and market expansion, as well as threats from increasing competition and concerns over internet safety. By formulating S-O, W-O, S-T, and W-T strategies, the research provides practical recommendations for enhancing customer engagement, improving operational systems, and maintaining market leadership. The findings contribute to the understanding of strategic marketing in Indonesia’s telecommunications industry and offer a roadmap for companies seeking to align internal capabilities with external dynamics.